2002
DOI: 10.1016/s0893-133x(01)00389-x
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Serotonin2A Receptor Antagonist, MDL100,907, Elicits a Specific Interoceptive Cue in Rats

Abstract: Employing a two-lever, food-reinforced, Fixed Ratio 10 drug discrimination procedure, rats were trained to recognize the highly-selective serotonin (5-HT) 2A receptor antagonist, MDL100,907 (0.16 mg/kg, i.p.) Drug discrimination procedures have been extensively used in the characterization of psychoactive agents, including drugs interacting with 5-HT reuptake sites (Millan et al. 1999b) and agonists at 5-HT 1A (Schreiber et al. 1995b) and 5-HT 3 (Glennon et al. 1992) receptors. Although it has proven difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
0
11
1
Order By: Relevance
“…Different groups of eight rats each were trained to discriminate between saline and either 0.56 mg/kg DOM, 1.0 mg/kg ketanserin, or 0.1 mg/kg MDL100907 while responding under a fixed ratio (FR) schedule of food presentation. The training doses of DOM, ketanserin, and MDL100907 were based on published reports of these drugs when they were used as training drugs or to antagonize drugs presumed to be acting at 5-HT 2A receptors (Schreiber et al, 1994;Dekeyne et al, 2002;Smith et al, 2002;Li et al, 2007). Daily sessions consisted of a 30-min timeout period, during which the chamber was dark and lever presses had no programmed consequence, followed by a response period, during which stimulus lights above both levers were illuminated and an FR 5 schedule of food presentation was active.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different groups of eight rats each were trained to discriminate between saline and either 0.56 mg/kg DOM, 1.0 mg/kg ketanserin, or 0.1 mg/kg MDL100907 while responding under a fixed ratio (FR) schedule of food presentation. The training doses of DOM, ketanserin, and MDL100907 were based on published reports of these drugs when they were used as training drugs or to antagonize drugs presumed to be acting at 5-HT 2A receptors (Schreiber et al, 1994;Dekeyne et al, 2002;Smith et al, 2002;Li et al, 2007). Daily sessions consisted of a 30-min timeout period, during which the chamber was dark and lever presses had no programmed consequence, followed by a response period, during which stimulus lights above both levers were illuminated and an FR 5 schedule of food presentation was active.…”
Section: Methodsmentioning
confidence: 99%
“…Several laboratories have established stimulus control with DOM (e.g., Glennon et al, 1983). Stimulus control also has been established with MDL100907 (Dekeyne et al, 2002), although this discrimination has not been used to explore possible inverse agonism by MDL100907; and stimulus control has been established between ketanserin and another drug (e.g., quipazine; Smith et al, 1995Smith et al, , 2002, although there are no reports of a discrimination between ketanserin and vehicle.…”
mentioning
confidence: 99%
“…A role of 5-HT 2A receptor blockade in the DS properties of mirtazapine also appears unlikely inasmuch as SB242,084, SB243,213, and S32006 all possess low affinity for 5-HT 2A receptors, and the highly selective antagonist at 5-HT 2A receptors, MDL100,907 and SR46349-B, failed to significantly substitute for mirtazapine. Nonetheless, it would be interesting to evaluate whether mirtazapine substitutes for a DS elicited by MDL100,907 itself and whether it blocks the interoceptive actions of the agonist, DOI, which are elicited via stimulation of 5-HT 2A receptors (Schreiber et al 1994;Dekeyne et al 2002). …”
Section: Discussionmentioning
confidence: 99%
“…Third, both mianserin and mirtazapine abolished a DS elicited by the α 2 -AR agonist, S18616 (Dekeyne and Millan 2006). Fourth, mianserin antagonized a DS elicited by the 5- CLZ Clozapine, SSRI selective 5-HT reuptake inhibitor, NARI noradrenaline reuptake inhibitor, Ant antagonist, PAG partial agonist HT 2A agonist, DOI (Yamamoto et al 1991;Smith et al 1990Smith et al , 2002Schreiber et al 1994) and substituted for the 5-HT 2A receptor antagonist, MDL100,907 (Dekeyne et al 2002;Dekeyne A and Millan MJ, unpublished observation). Finally, mianserin shared the DS properties of the 5-HT 1A agonist, flesinoxan (Herremans et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of M100907 as an antagonist of hallucinogen-induced stimulus control in the rat was first demonstrated by Schreiber et al (1994) for DOI and has now been extended to include, among others, LSD, 5-MeO-DMT, and DOM. An interesting complication was added by Dekeyne et al (2002Dekeyne et al ( , 2003 who observed that M100907 can establish stimulus control in the rat and suggested that the effect is mediated by antagonism of 5-HT 2A receptors with possible involvement of alpha 1 adrenoceptors and other yet to be identified mechanisms.…”
Section: Neurochemical Bases Of Stimulus Control By Hallucinogensmentioning
confidence: 99%